O Optimalisasi Bimbingan Belajar dalam Meningkatkan Hasil Belajar Siswa SD di Desa Sungai Kambat: Optimizing Tutoring Programs to Enhance Elementary School Students' Learning Outcomes in Sungai Kambat Village - Wahidah, Wahidah; Zaitun, Siti; Mustaqimah, Umi; Sumiati, Sumiati; Noorsa'adatina, Noorsa'adatina; Winda, Winda; Fajrianor, Muhammad; Maulana, M. Fajar; Rizky, Muhammad; Rahman, Aulia (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
Kuliah kerja Nyata (KKN) program aims to encouraging  students to contribute directly to the community by implementing the Tri Dharma of Higher Education, one of which is through increasing student motivation and learning outcomes. Based on initial observations, the motivation and learning outcomes of elementary school students in Sungai Kambat Village are still low. This is due to the lack of reading, writing, and arithmetic skills possessed by students. For this reason, it is necessary to carry out tutoring activities as one of the Kuliah Kerja Nyata (KKN) programs to improve the motivation and learning outcomes of elementary school students. The method implemented through sequential stages consists of observation and interviews, licensing, implementation, and evaluation. This tutoring activity is carried out at the Real Work Lecture student post every morning from Monday to Thursday at 10:30-12:00 WITA by teaching material about reading, writing, and counting. The results of tutoring activities show that there is an increase in learning outcomes and learning motivation among elementary school students in Sungai Kambat Village. Tutoring activities can be an alternative to improving student motivation and learning outcomes in Sungai Kambat Village.